Dynamics of Transcultural Communication through Language Use in Multicultural Islamic Boarding Schools: A Comparative Study: Penelitian - Putra Darma, Virga; Auliyah, Nazwa; Dinda Afrilla, Nasya (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research analyzes the dynamics of transcultural communication and language use in two multicultural Islamic educational institutions, Pondok Pesantren Buntet and Pondok Qur'an Birruna Putri, through a comparative study of their contrasting language policies and practices. Using a qualitative approach, this study reveals how different language policies fundamentally shape the intercultural communication and adaptation experiences of santri. At Pondok Pesantren Buntet, the dominance of the Cirebon regional language encourages organic and informal language adaptation, where linguistic misunderstandings turn into positive experiences that strengthen relationships and foster inclusivity based on traditional family values. In contrast, Pondok Qur'an Birruna Putri with its strict obligation to use Arabic and English, demonstrates accelerated foreign language acquisition and communication unification amidst regional diversity, turning linguistic challenges into a drive for understanding and building unity through a universal language. Overall, this study highlights that the diversity of santri backgrounds is both a strength and a challenge, and the leadership role of kyai and ustadz/ustadzah is crucial in instilling values of tolerance and unity that transcend cultural and linguistic boundaries. This research contributes to a deeper understanding of the management of transcultural communication in pesantren through diverse language strategies.